Isotope dilution analysis of Ca and Zr in apatite and zircon (U‐Th)/He chronometry. (6th May 2016) - Guenthner, William R.; Reiners, Peter W.; Chowdhury, Uttam
Abstract: Because radiation damage influences He diffusivity, correlations between (U‐Th)/He ages and effective uranium (eU, eU = U + 0.235 × Th) concentrations of single apatite and zircon grains are important for understanding thermal histories. Here we describe a method for quantifying eU concentrations in apatite and zircon grains using isotope dilution ICP‐MS measurements of Zr and Ca and stoichiometry of zircon (ZrSiO4 ) and apatite (Ca5 (PO4 )3 F) to obtain grain masses. Combined with independent U and Th measurements, these yield eU concentrations not based on the traditional morphologic measurements and assumptions. Additional benefits of this method include correct identification of an apatite or zircon and volume estimates for crystal shards. In some cases, this method gives eU concentrations consistent with those calculated with the morphologic approach, but often significant differences are observed between concentrations calculated from the two methods. Differences in eU concentrations for our apatite grains are greater and less than morphology estimates, and the majority are between 0.7 and 31%. With the exception of two grains, all of our zircon grains have differences between 3 and 34% less than morphology estimates. These differences could result from incorrect grain width measurements, mischaracterized grain shape, or incorrect volume calculations of the pure mineral phase due to inclusions. These morphologic errors—combined with evidence for the accuracy of our isotope dilution method from analyses of reference materials—suggest that eU concentrations calculated from morphology may often be significantly inaccurate. Finally, we demonstrate that differences between the two measurements of eU cause age‐eU correlation variations for representative thermal histories. Key Points: Method for determining eU concentration from ID measurements of Zr and Ca Our method results highlight issues with traditional morphology‐based approach Implications for thermal histories determined from age‐eU correlations